Eksistensi Tari Sufi pada Komunitas Al-Fairouz di Kota Medan - Mega Nurvinta (Universitas Negeri Medan, 2016)
This journal aims to describe the existence of Sufi Dance AtCommunity Al Fairouz In the city of Medan include: (1) history, (2)function, (3) a presentation of Sufi dance at Al Fairouz community inMedan.This study used a qualitative descriptive approach. This research datais the history, function, and form of presentation of Sufi dance at AlFairouz community in Medan. The data used is the Sufi dance on AlFairouz community in Medan. Data were collected with a populationof 11 people consisting of 1 figure and 10 dancers Sufi, observation,interview, and literature study. Data were analyzed using descriptivetechniques.The results of this study as follows. 1) Background Sufi Dance on AlFairouz community that started when there Bersholawat Muslimevent, along with Habib Sheikh and Sheikh Hisham Kabbani ofAmerica, which at the time makhalul qiyam where there are fewdharwish (pupil thoriqoh) dance around in circles. 2). The existenceof Sufi dance at Al Fairouz community named as one of the Sufi dancecommunity that organizes the only one in the city of Medan. Theexistence of the Sufi dance is not very well known by the people of thecity of Medan. 3) Function Sufi dance at Al Fairouz community,namely as a medium persembahaan and worship, as the entertainmentmedia, as the media spectacle or show. 3) The form of presentation ofSufi dance at Al Fairouz community, namely (a) motion, (b) the musicor accompaniment, (c) cosmetology, (d) the pattern of the floor, (e)the stag